Anmeldelser - Holme Hansen, Thomas (Danish Yearbook of Musicology, 2011)
Review of: Zdravko Blažekovic and James R. Cowdery (eds.): Liber Amicorum. Festschriften for Music Scholars and Nonmusicians 1840–1966. RILM Retrospective Series, 5; New York: RILM, 2009. Zdravko Blažekovic and Barbara Dobbs Mackenzie (eds.): Music’s Intellectual History. RILM Perspectives Series, 1; New York: RILM, 2009